KONSEP MAQOMAT DAN AKHWAL - Abdul Wahab Syakhrani; Nadia Nursyifa; Nurul Fithroti (MUSHAF JOURNAL: Jurnal Ilmu Al Quran dan Hadis, 2024)
Maqamat is the plural form of the word maqam, which literally means rank or degree. In English, maqamat is referred to as stations or stages. Meanwhile, according to the terms of the science of Sufism, maqamat is the position of a servant before Allah, which is obtained through worship, mujahadat and other things, spiritual training and (relationship) that is not broken with Allah SWT. According to Al-Thusi's view, namely: "Ahwal is a state of the heart that always makes remembrance, and it is not seen from the methodology of mujahadah and exercises as previously mentioned. Ahwal is like: feeling watched by Allah SWT, feeling close to Allah SWT, feeling of love, fear, hope, longing, calm, confident and others". The types of Maqamat are divided into 9, among others: Al-Taubah, AlIstiqomah, Al-Wara', Al- Zuhd, Al-Faqr, Al-Shabr, Al-Tawakkal, Al-Rida, and Al -Mahabbah. While the types of Ahwal are divided into 8, namely: AlMuhasabah & al-Muroqobah (alert & introspective), Al-'Isyq (longing), Al-Uns (intimate), Thuma'ninah, Musyahadah, Yaqin, Mahabbah, Raja' and Khauf.